Islam Dan Pencarian Identitas Politik (Ambiguitas Sistem Khilafah dalam Institusi Politik Islam) - ma'shum, ma'shum (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
Often excessive if Muslims presupposes a past glory rests only on thecaliphate system as Khulaf?u ar-r?syid?n and then refer to it as (the only) areaideal representation of the Islamic state without going through the lengthy studyand adequate correction. One important note that the formulation of systemleadership be after the Prophet has inspired the formulation of a long and contentious in the Islamic system of government with reference to the spirit that they built through the first three principles, namely, emphasizing deliberationin solving political and social issues. Secondly, giving priority to be a leader tothe people who have and are accepted by most people, and the Third, by thepublic statements of loyalty in following their leadership expressed in the formof initiation.